AI-enhanced STEAM-based physics towards a teacher education framework for cognitive adaptability, creative problem solving, and green skills - Basagre, Rey Mark G.; Monterola, Sheryl Lyn C.; Sasing, Monalisa T.; Salubayba, Teodora M.; Que, Elenita N.; Roxas-Villanueva, Ranzivelle Marianne (Quezon City College of Education, University of the Philippines Diliman, 2025)
The combination of STEM approach and artificial intelligence offers an innovative teaching approach that could enable students to master concepts while equipping them with useful 21st-century skills in the unprecedented pace of the world’s technological growth. This study investigated the effects STEAM-Based Physics with Artificial Intelligence (STPAI) on pre-service teachers’ cognitive ability, creative problem solving, and green skills towards a pre-service teacher education framework. From the total of 134 pre-service teacher respondents, this explanatory sequential mixed-method research gathered quantitative data through a pre-test and post-test administered to three groups exposed to teaching approaches namely Conventional Approach in Teaching Physics (CATP), STEAM- Based Physics (STP), and STEAM-Based Physics with Artificial Intelligence (STPAI) to determine its effects on pre-service teachers’ cognitive adaptability, creative problem solving, and green skills. Qualitative data were gathered through focus group discussions and analysis of student outputs. Data analysis procedures such as ANOVA, Kruskal-Wallis H-Test, Multiple Regression, Thematic Analysis, and Content Analysis were used to interpret the collected data.

The results revealed a significant difference in pre-service teachers’ cognitive adaptability (x^2 (2) = 26.05, p < .001), creative problem solving (x^2 (2) = 26.00, p < .001), and green skills (x^2 (2) = 24.31, p < .001) when exposed to STP and STPAI approaches compared to the conventional approach in teaching physics, while there were no significant differences found between STP and STPAI (p = 0.822).

Cognitive adaptability was significantly predicted by creative problem solving and green skills when pre-service teachers were exposed to STEAM-Based Physics teaching approach (F (2,42) = 4.654, p = 0.000), but not under the conventional approach in teaching physics (F (2,42) = 0.160, p = 0.873), and STEAM-Based Physics with Artificial Intelligence teaching approach (F (2,42) = 1.222, p = 0.228). Creative problem solving was predicted by cognitive adaptability and green skills (F (2,42) = 4.606, p = 0.000; F (2,42) = 3.373, p = 0.002; F (2,42) = 4.425, p = 000) as green skills was significantly predicted by cognitive adaptability and creative problem solving (F (2,42) = 4.613, p = 0.000; F (2,42) = 5.088, p = 0.000; F(2,42) = 4.508, p 0.000) when pre-service teachers’ were exposed to the three teaching approaches.

Green skills had a significant direct effect on creative problem solving across the three teaching approaches (p = 0.038; p = 0.018; pl = 0.002) and on cognitive adaptability (p = 0.020) under the STEAM-Based Physics. Creative problem solving significantly influenced green skills in STEAM-Based Physics (p = 0.024), and STEAM-Based Physics with Artificial Intelligence (p = 0.004) teaching approaches Further, cognitive ability was found to mediate (p = 0.050; p = 0.055) the bidirectional interactions of green skills and creative problem solving when students are exposed to the conventional approach in teaching physics.

A teacher education framework for the implementation of a STEAM-Based Physics with Artificial Intelligence teaching approach was developed, structured around learning intents, contents, experience, and assessment, fostering pre-service teachers’ cognitive adaptability, creative problem solving, and green skills.
Dissertation
Includes bibliographical references (325-333 leaves)
Keywords: Physics— Study and teaching -- Philippines; Science— Study and teaching -- Philippines; Artificial Intelligence